KEPEMIMPINAN TRANSFORMASIONAL POLITEKNIK LP3I JAKARTA - Suprayogi, Bambang; Ridwansyah, Muhammad; Razak, Abdur (POLITEKNIK LP3I JAKARTA, 2026)
This study seeks to analyze the transformational leadership style of LP3I Jakarta Polytechnic. The purpose of this research is to learn more about the qualities that a good leader must possess in order for a leader to perform his duties effectively and educational programs to run smoothly. This study uses a literature study technique by analyzing various leadership journals and books. The findings of this study suggest that once the characteristics of an ideal leader have been identified, they must be adapted to fit the chosen leadership model. As a result of the analysis of various literatures, researchers have at least two conclusions: 1) Leadership is a person who has the ability, the power of art to influence, give aspirations, and direct the behavior of a person or organization in its work in a way of obedience, trust, honor, and enthusiastic cooperation in achieving the goals of mutual education. 2) to achieve educational goals optimally, effectively, and efficiently, it requires leadership that is responsible and understands the main tasks and functions effectively and efficiently